Synthesis and characterization of molybdenum based nanocomposites film for water splitting applications / Choong Zheng Lin - Choong , Zheng Lin (2023)
The molybdenum-based nanocomposite films in the form of Mo2S3/MoP2 composite were prepared by using AACVD method with the single source precursor of [CpMo(CO)2(S2P(SPhMe)2)] (1) (Cp = C5H5) in THF at 0.01 M under argon gas flow in different deposition conditions inclusive of different deposition temperatures (450 °C, 550 °C, 650 °C), duration of deposition time (20 mins, 30 mins and 40 mins), different volume of precursor solution (10, 15, 20 and 25 mL) and carrier gas flow rate (0.3 and 0.5 SCFH). The bandgap energy values obtained in the visible light spectrum were close to the literature values for Mo2S3 and MoP2 at ~2.3 eV and ~2.8 eV, respectively. The deposition conditions had no significant effect on the band gap of the films. Among all the films synthesized for this study, the 20 ml/30 mins film fabricated at 550 °C with carrier gas flow rate of 0.3 SCFH generated the best current density of 10 mA/cm2 at 250 mV due to wide distribution of MoP2 grains across the film, which promoted significant interaction between Mo2S3 and MoP2 particles in the heterojunctions that provide sufficient amount of active sites for catalysing hydrogen evolution reaction (HER). With a favourable surface roughness, Rq of 106.4 nm resulted from suitable mean particle size of 1000-3000 nm coupled with film thickness of 968 nm had provided the film with abundance of active sites, which have the propensity to undergo HER reaction in 0.25 M H2SO4 acidic media (pH 0.95) owing to a low electron transport resistance of 0.715 kΩ. Based on the Tafel slopes, the approximate overall extracted values of 120 mV/dec for all the fabricated films indicated that Volmer reaction was the rate determining step in HER. Films fabricated at 450 °C with different volumes of precursor solution and deposition times were chosen as a study model for electrochemical studies in alkaline media prepared by mixing 0.25 M of Na2S and 0.35M of Na2SO3 (pH 11.71). It was found that oxygen evolution reaction (OER) was more significant than HER in alkaline media. However, the 20 mL/20 mins film fabricated at 450 °C with the carrier gas flow rate of 0.5 SCFH exhibited a large Tafel slope of 190 mV/dec and a very large onset potential of 1.14 V in OER. Therefore, Mo2S3/MoP2 composite material may not be a suitable electrocatalyst for OER activity in alkaline media. The electrochemical studies from fabrication of films under different synthesis conditions mentioned above via AACVD could be applied to determine an appropriate morphology that is suitable as electrocatalysts for water splitting application.